4th generation R&D managing knowledge, technology, and innovation - Miller, William L. 1944- (John Wiley & Sons, 1998)
A sweeping and insightful analysis of an architecture for innovation in the knowledge economy. Technologists, strategists, and organizational architects will all find this book worth reading, as will students of the modern organization.